EGFR-antagonistic affibody-functionalized Pt-based nanozyme for enhanced tumor radiotherapy - Haijun Wang; Xichen Zhao; Heng Zhang; Xianwen Zou; Dianlong Jia; Wenjian Liu; Baoqing Tian; Dandan Yuan; Yihui Li; Yao Zhu; Fan Zhang; Yongsi Dai; et al. (Materials Today Advances, 2023)
Clinical radiotherapy (RT) is severely limited by hypoxic tumor microenvironment and a lack of targeting precision. Therefore, it is crucial to develop highly efficient radiosensitizers to enhance RT efficacy. Herein, a novel kind of epidermal growth factor receptor (EGFR)-antagonistic affibody-functionalized Pt-based nanozyme for RT sensitization to EGFR-positive tumors was developed. In this study, porous platinum nanoparticles (pPt NPs) featuring catalase (CAT)-like activity and strong radiation energy absorption ability were first synthesized. Then, a thin biomimetic polydopamine (PDA) layer was coated on pPt NPs to optimize its biocompatibility as well as provide a reactive surface. Finally, a dimeric EGFR-antagonistic affibody called ZEGFR expressed by the Escherichia coli (E. coli), was conjugated to pPt@PDA NPs (termed pPt@PDA-ZEGFR NPs) to precisely recognize EGFR-positive A431 tumors. Under the navigation of ZEGFR, superior tumor homing was achieved with these Pt-based nanozymes, which was ascribed to EGFR receptor-mediated endocytosis. As high-Z metal NPs exhibit an inherently strong ability to absorb radiation energy and catalyze endogenous H2O2 in tumors, the pPt@PDA-ZEGFR NPs demonstrated superb therapeutic efficacy; specifically, the NPs significantly inhibited HIF-1α expression and increased RT-induced DNA damage. Furthermore, the biosafety of these Pt-based nanozymes was good during short-term treatment. In summary, EGFR-antagonistic affibody-functionalized Pt-based nanozymes are promising radiosensitizers for the precise therapy of EGFR-positive tumors.